Implementation of the Mim-Mem Method (Mimicry Memorization Method) in Efforts to Strengthen Arabic Speaking Skills - Iva Setywati; Lili Musyafa’ah (Journal of Practice Learning and Educational Development, 2026)
This study was motivated by the limited Arabic speaking proficiency of female students at the Al-Iman Situbondo *Madrasah Diniyah* (Islamic religious school), a result of monotonous teaching methods and difficulties with vocabulary memorization. The research aimed to identify obstacles and analyze the impact of implementing the Mimicry-Memorization (Mim-Mem) method on strengthening *Maharah al-Kalam* (speaking skills). Employing a qualitative case study approach, data were gathered through in-depth interviews, participant observation, and documentation involving seven students. The results indicate that systematic drill techniques effectively mitigated the interference of local dialects and significantly boosted the students' self-confidence. A key finding reveals that intensive imitation and repetition successfully transformed passive behavior into active, communicative engagement. In conclusion, the Mim-Mem method proved to be a tactical solution for accelerating vocabulary retention and articulation fluency, thereby offering a practical contribution to the development of Arabic language teaching methodologies within traditional educational institutions.